The word means for expression of modal possibilities in indication of Albanian verbs - T A Blerina (Vestnik Rossijskogo universiteta družby narodov. Seriâ Lingvistika, 2010)
In this article, on basis of comparative analysis between Albanian and Russian languages are studied the word means for expression of modal possibilities in indication of albanian verbs.